SOME ATTRACTIVE FACTORS TO FOREIGN DIRECT INVESTMENTS IN ALBANIA - Blerta (Spahija) Dragusha; Elez Osmani (European Scientific Journal, ESJ, 2012)
Foreign direct investments are very important for the implementation of strategic reforms, transfer of advanced technologies and managerial methods, thereby stimulating economic growth in developing countries and in particular, transition economies such as Albania is. During the last years, Albania experienced an increase in foreign investors. interest in a wide range of sectors, with energy generation, telecommunication, cement production, mining, oil and industrial parks heading the list. However, the major obstacle factors for FDI inflows seem to remain the same: pervasive corruption, weak law enforcement, poor rule of law, lack of developed infrastructure, lack of a reliable energy supply and insufficiently defined property rights. Determining the factors that attract FDI, and furthermore identify the main characteristics of the host country's economy, are essential to understand the reason of FDI inflows to a country or region. In the empirical perspective, various studies give different results. More specifically, this paper has focused on determining the factors for and against FDI in Albania.